Kekuatan Pasar (Market Power) dan Pangsa Ekspor Produk Ban (HS4011) Indonesia dan Negara Pesaing di Malaysia dan Filipina - Zainuddin Zainuddin (Ekonomis: Journal of Economics and Business, 2020)
The exporters of Indonesian and Thailand tire products have the same capability in price mark-ups in the Malaysian market. The price mark-up capability of tire exporters from Indonesia, Thailand and China is greater than the domestic tire industry in the Philippines. However, China has a greater share of tire exports in the Malaysian and Philippine markets and is likely related to China's ability to be able to increase the export composition of various types of tires. Indonesia needs to encourage the domestic tire industry to increase the production capacity of various types of tires through investment and relocation of the tire industry to Indonesia amid the downward trend in China's manufacturing industry. Need to develop tire products for the types of trucks, buses, tractors and heavy equipment that are often used in the construction, agriculture, mining and cargo transportation ports to enlarge market share in Malaysia and the Philippines because Indonesia has competitiveness from the aspect of raw materials. The potential export of various types of tires in the two export destination countries is a challenge to increase the number of exports of Indonesian tire products.